Bringing in care planning conversations for patients whose recovery is uncertain: learning from the AMBER care bundle. Issue 1 (1st June 2011) - Morris, M; Briant, L; Chidgey-Clark, J; Shouls, S; Carey, I; Hopper, A; Robinson, C
Abstract : 60 per cent of people in our inner city area die in an acute hospital. The hospital provides good care to patients known to be dying through the Liverpool Care Pathway. Delays in recognising that a patient may be end of life prevents timely patient and family involvement in planning care. Some of these delays relate to hospital staff having difficulties in managing uncertainty, as patients receive full active treatment. This can result in distress and preferences not being met. The team designed and develop the AMBER care bundle for patients who may be receiving active treatment but whose recovery is uncertain. The care bundle comprises four elements: ▶ Clear medical plan ▶ Clear escalation plan ▶ Nurses agree with medical plan ▶ Patient/family meeting. The care bundle complements, but does not replace existing care pathways. Staff make key decisions around ceilings of treatment and care and treatment preferences involving patients and their families. Patients are identified via ward rounds, nursing handover, multi-disciplinary meetings and by the patient safety team. To date 122 patients have received the AMBER care bundle. 48% were transferred to the community from hospital. 78% died in their preferred place of care. Staff often needed initial training or support to hold the family meetings. Expert facilitation helped to overcome barriers. Patients and family feedback has been positive. There have been benefits to team working and within team communication around this important patient group.